2021
DOI: 10.21203/rs.3.rs-266574/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

More Than 50 Long-Term Effects of COVID-19: A Systematic Review and Meta-Analysis

Abstract: Background. COVID-19, caused by SARS-CoV-2, can involve sequelae and other medical complications that last weeks to months after initial recovery, which has come to be called Long-COVID or COVID long-haulers. This systematic review and meta-analysis aims to identify studies assessing long-term effects of COVID-19 and estimates the prevalence of each symptom, sign, or laboratory parameter of patients at a post-COVID-19 stage. Methods. LitCOVID (PubMed and Medline) and Embase were searched by two independent res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
198
1
63

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 303 publications
(276 citation statements)
references
References 7 publications
14
198
1
63
Order By: Relevance
“…Numerous research groups reported widespread persisting symptoms in COVID-19 patients for up to 6 months after SARS-CoV-2 infection (70,75,(123)(124)(125)(126)(127)(128)(129)(130)(131)(132)(133)(134)(135)(136)(137)(138)(139)(140)(141)(142). They also described practice on the management of post-acute COVID-19 and performed comprehensive analyses of health-related quality of life (70,75,123).…”
Section: Widespread Persistent Symptomsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous research groups reported widespread persisting symptoms in COVID-19 patients for up to 6 months after SARS-CoV-2 infection (70,75,(123)(124)(125)(126)(127)(128)(129)(130)(131)(132)(133)(134)(135)(136)(137)(138)(139)(140)(141)(142). They also described practice on the management of post-acute COVID-19 and performed comprehensive analyses of health-related quality of life (70,75,123).…”
Section: Widespread Persistent Symptomsmentioning
confidence: 99%
“…They also described practice on the management of post-acute COVID-19 and performed comprehensive analyses of health-related quality of life (70,75,123). Furthermore, numerous editorials, reviews, news articles, clinical updates, narrative interviews, and focus groups have been published to explore what it is like to live with long-term COVID-19, also trying to emphasize the putative pathophysiology, risk factors, and treatments (124)(125)(126)(127)(128)(129)(130)(131)(132)(133)(134)(135)(136)(137)(138)(139)(140)(141)(142). Two cohort studies on severe/critical COVID-19 patients reported persistent physiological impairment and decrease in quality of life in more than half of the patients at up to 6 months of follow up (77,100).…”
Section: Widespread Persistent Symptomsmentioning
confidence: 99%
“…Unter mehr als 50 beschriebenen Post-COVID-Symptomen scheint die Fatigue das häufigste zu sein [ 21 ]. Jüngeren wird in der Regel Ruhe, Stressreduktion, keine sportlichen Aktivitäten und Entspannung empfohlen.…”
Section: Medizinische Empfehlungenunclassified
“…There is an increasing number of individuals who suffer from postacute COVID-19, a syndrome characterized by persistent symptoms and/or delayed or long-term complications beyond 4 weeks from the onset of symptoms [17,18], including anosmia, muscular weakness, chronic fatigue, cognitive and sleep disturbances, chest pain, palpitations, and hair loss. A systematic meta-analysis of cohort studies [19] revealed prolonged effects after acute COVID-19 in 80% of the study population aged 17-87 years. Persistent respiratory symptoms, rather independent of the severity of initial lung involvement [20], have often been recorded and follow-up of large groups of patients indicated breathlessness to be one of the most frequent postinfectious health issues [21,22].…”
Section: Discussionmentioning
confidence: 99%